Characterization of the Strong Metric Subregularity of the Mordukhovich Subdifferential on Asplund Spaces - J. J. Wang; W. Song (Abstract and Applied Analysis)
We mainly present several equivalent characterizations of the strong metric subregularity of the Mordukhovich subdifferential for an extended-real-valued lower semicontinuous, prox-regular, and subdifferentially continuous function acting on an Asplund space.